Stabilitas Hasil Calon Varietas Jagung Hibrida Toleran Nitrogen Rendah - Priyanto, Slamet Bambang; Wicaksana, Noladhi; Rachmadi, Meddy (Universitas Bangka Belitung, 2021)
The improvement of low nitrogen tolerant hybrid maize face on genotype x environment the genotype x environment interaction caused a genotype unable to maintain its appearance under suboptimal conditions. it caused the breeders difficult to choose varieties that are stable at optimal and suboptimal conditions. The using of simultaneous stability analysis methods can provide more authentic stability information. This study aims to 1) determine the yield stability of the promising low N tolerance hybrid maize varieties, 2) to obtain varieties that have high yield and stability and under optimal and sub-optimal conditions. This research was conducted at Bajeng Experimental farm, Gowa, South Sulawesi. The research was arranged in a split-plot design with two replications. Three levels of fertilizer N (N0 = 0 kg N ha-1, N1 = 100 kg N ha-1 and N2 = 200 kg N ha-1) as the main plot and 39 genotypes of maize (36 hybrids resulting from crosses of low N and 3 checks varieties Nasa 29, Bisi 18 and Jakorin 1) as the subplot. The variable measured was grain yield. The yield stability analyses were performed by Francis and Kannenberg, Finlay and Wilkinson, Eberhart and Russel, and GGE Biplot methods. The results showed that there were no genotypes stable in overall the four methods, but three genotypes considered as stable genotype based on two methods. H5, H6 and H15 genotype were the genotypes with high stability and high yield. The three genotypes had the opportunity to be released as a low Nitrogen tolerant maize hybrid.